Colonization resistance is dispensable for segregation of oral and gut microbiota - Rashidi, Armin; Koyama, Motoko; Dey, Neelendu; McLean, Jeffrey S.; Hill, Geoffrey R. (BMC medical genomics, 2023)
The oral and colonic microbiota are distinct in healthy individuals. However, this distinction is diminished in common diseases such as colon cancer and inflammatory bowel disease, suggesting a potential pathogenic role for oral bacteria when ectopically colonized in the gut. A key mechanism for the segregation of oral and colonic microbiota niches is thought to be microbiota-mediated colonization resistance whereby the commensal gut microbiota outcompete and eliminate the ingested oral bacteria. We tested this theory by analyzing exact amplicon sequence variants generated from concurrent fecal and oral samples from healthy volunteers exposed to a brief course of a single antibiotic (cohort 1), acute leukemia patients (cohort 2), and stem cell transplant recipients (cohort 3). Cohorts 2 and 3 represent extreme clinical scenarios with respect to antibiotic pressure and severity of gut microbiota injury. While mild antibiotic exposure in cohort 1 was not sufficient for colonization of any oral bacteria in the gut, even with extreme antibiotic pressure and severe gut microbiota disruptions in cohorts 2 and 3, only one oral species in each cohort colonized the gut. Colonization resistance is dispensable for segregation of oral and colonic microbiota in humans. This finding implies that the presence of oral bacteria in the distal gut in diseases such as colon cancer and inflammatory bowel disease is not driven by impaired colonization resistance.